2017
DOI: 10.1002/2017ja024132
|View full text |Cite
|
Sign up to set email alerts
|

On the historical origins of the CEJ, DP2, and Ddyn current systems and their roles in the predictions of ionospheric responses to geomagnetic storms at equatorial latitudes

Abstract: In this short letter, we recall the differences between the counter electrojet (CEJ), which is a phenomenon observed on the magnetically quiet days and the disturbance dynamo (Ddyn), which can be observed during and after a geomagnetic storm. The CEJ is well known to occur near the geomagnetic dip equator. It can be identified by a reversal in the horizontal component (H) of the geomagnetic field daily regular variations. In contrast to equatorial electrojet (EEJ) that flows eastward in the daytime, the CEJ is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…We find that although PP signature remained the same throughout, Ddyn signature showed a longitude dependence for all the three storms. This spectral technique is also suggested by Amory- Mazaudier et al (2017).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We find that although PP signature remained the same throughout, Ddyn signature showed a longitude dependence for all the three storms. This spectral technique is also suggested by Amory- Mazaudier et al (2017).…”
Section: Discussionmentioning
confidence: 89%
“…In the late recovery phase, auroral indices were quiet (24 and 25 March 2015) in the first 12 hr and there were no fluctuation in E y component. This demonstrates that at this stage the Ddyn process becomes the dominant mechanism that restructures the ionospheric parameters (Amory‐Mazaudier et al, ). Similar observations of Ddyn were reported in the late recovery phase of the storm (Fathy et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…This reversed electrojet (Mayaud, ) sometimes occurs during cases of rapid decrease in magnetospheric penetrating electric field during sudden northward turning (Kikuchi et al, ). Amory‐Mazaudier et al () have, however, warned that such reversed electrojet are related to Ddyn and should not be confused with quiet time CEJ.…”
Section: Discussionmentioning
confidence: 99%
“…DP2 and Ddyn signals can be extracted from Diono using appropriate filters and taken into consideration the characteristics of each signals. It has been shown that short‐term oscillations of about 3‐hr periods are characteristics of the DP2, while diurnal oscillations producing a reversal in the daily variation of the Earth's magnetic field are associated to Ddyn (Amory‐Mazaudier et al, ; Nava et al, ). Nava et al () further used a high‐pass filter to extract periods lower than 4 h from Diono and a band‐pass filter to separate diurnal periods corresponding to Ddyn.…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
“…The equatorward vortex resembles an anti‐Sq current system (Le Huy & Amory‐Mazaudier, ; Zaka et al, ), flowing essentially opposite to the quiet day currents and, therefore, driving westward electric field perturbations during daytime. The DD causes global scale magnetic disturbances (Fambitakoye et al, ) which have been characterized by latitudinal profile of D dyn (Amory‐Mazaudier et al, ; Le Huy & Amory‐Mazaudier, ) that is defined as follows, Ddyn=normalΔHSRSYMH, wherein Δ H , S R , and SYMH are overall fluctuations in the horizontal geomagnetic field above various components of Earth's internal magnetic field magnetic field, magnetic field fluctuations due to quiet time ionospheric dynamo, and magnetic field induced by the ring current (and corrected for magnetic latitude), respectively. In this mathematical relationship, the contributions from the other ionospheric (DP2) and magnetospheric currents (e.g., Chapman‐Ferraro and Tail currents) are assumed to be negligible during the recovery phase of the storm.…”
Section: Introductionmentioning
confidence: 99%